Evolution of drug therapy for classical Hodgkin lymphoma - N. Y. Samaneva; I. B. Lysenko; N. V. Nikolaeva; E. A. Kapuza; I. A. Kamaeva; Y. S. Gaysultanova; A. V. Tishina; T. F. Pushkareva (Южно-Российский онкологический журнал)
Hodgkin's lymphoma is a malignant disease of the lymphatic system. Hodgkin's lymphoma was first described by Dr. Thomas Hodgkin in 1832 and later named “Hodgkin's disease” by Samuel Wilkes. Hodgkin's lymphoma accounts for about 24 % of all lymphomas. Hodgkin's lymphoma is classified as classical and nodular lymphoid-predominant (Nodular type of lymphoidpredominant Hodgkin's lymphoma). Classical Hodgkin's lymphoma includes the following histologic variants: nodular sclerosis variant (types I and II), mixed cell variant, classic lymphocyte-rich variant, and rare lymphoid depletion variant. Epidemiological and serological studies showed the involvement of the Epstein-Barr virus into Hodgkin's lymphoma etiology, since its genome was found in the study of the biopsy material samples from patients with Hodgkin's lymphoma. A relationship with the human immunodeficiency virus (HIV) was revealed as well, and patients infected with HIV have a significantly increased risk of developing Hodgkin's lymphoma compared to healthy people. An in-depth study of the Hodgkin's lymphoma pathophysiology revealed new therapeutic targets in the treatment of this disease. All these discoveries changed the understanding of the Hodgkin's lymphoma pathogenesis, and were important for the development of new methods of treatment. The history of therapy begins on the cusp of the 19th and 20th centuries. Over the past four decades, achievements in radiation therapy and combined chemotherapy have significantly improved overall survival of patients with Hodgkin's lymphoma. Currently, more than 80 % of patients under 60 years old with first diagnosed Hodgkin's lymphoma can be cured from this disease after first-line chemotherapy.